Perceiving the equation of state of Dark Energy while living in a Cold Spot - Valkenburg, Wessel (Journal of cosmology and astroparticle physics, 2012)
The Cold Spot could be an adiabatic perturbation on the surface of last scattering, in which case it is an over-density with comoving radius of the order of 1 Gpc. We assess the effect that living in a similar structure, without knowing it, has on our perception of the equation of state of Dark Energy. We find that structures of dimensions such that they could cause the Cold Spot on the CMB, affect the perceived equation of state of Dark Energy possibly up to ten percent.